Physiological maturation stage of cervical vertebrate index in cleft lip/palate and non-cleft lip/palate patients - Wenti Komala; Endah Mardiati; Eky Soeria Soemantri; Isnaniah Malik (Majalah Kedokteran Gigi Indonesia, 2018)
Cleft lip and palate is one of the most common congenital anomalies. Cleft lip and palate patients encounter growth problems in lip and palate area, although their overall growth and development remains unknown. Cervical vertebral maturation are indicators of physiological maturation used in interceptive treatment and orthognathic surgery. The present study aims to determine physiological maturation stage of cervical vertebrae maturation index in cleft andnon-cleft patients. Lateral cephalogram of 26 cleft patients and 27 non-cleft patients with a range of chronological age from 8-16 years old were involved. The cervical vertebrae maturation were analyzed in six stages of cervical vertebrae maturation method of Hassel and Farman. Data were analyzed using t-test (p≤ 0.05). The result shows that physiologicalmaturation stage of cervical vertebrae maturation index in cleft and non-cleft patients has no significant difference in stage acceleration (p= 0.38), stage transition (p= 0.41) and deceleration (p= 0.39). Likewise, there is no significant difference in physiological maturation stage of cervical vertebrae maturation index between cleft and non-cleft patients.